Big Questions, Little Answers: Terrorism Activity, Investor Sentiment and Stock Returns - Konstantinos Drakos (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
Motivated by the investor sentiment literature and assuming that terrorist activity influences investor mood the paper explores whether terrorism exerts a significant negative impact on daily stock market returns for a sample of 22 countries. The employed empirical specifications are based on flexible versions of the World CAPM allowing for autoregressive conditional heteroscedasticity. The results suggest that terrorist activity leads to significantly lower returns on the day of terrorist attack occurrence. In addition, the negative effect of terrorist activity is substantially amplified as the level of psychosocial effects increases. On the one hand this evidence sheds light to the underlying mechanism via which terrorism affects stock markets while on the other hand provides further empirical support for the sentiment effect.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: C33; E44; G15; 330; Sentiment; Terrorism; Stock Market; Panel; Pooled Panel ARCH